APLIKASI ASAP CAIR DARI KAYU LEBAN (Vitex pubescens Vahl) UNTUK PENGENDALIAN JAMUR PADA BENIH TUSAM (Pinus merkusii Jungh et de Vriese) SECARA In Vitro - Priyamto, Singgih; Oramahi, Hasan Ashari; dina, wah; Diba, Farah (JURNAL HUTAN LESTARI, 2013)
The research aimed to know the fungus isolated fromtusam seed and utilization of liquid smoke from leban wood with various concentration and pyrolysis temperature to overcome the fungus. This research was conducted in Wood Technology Laboratory of Forestry Faculty Tanjungpura University. The method used at this research contain of two factors. First factor is concentration of Laban liquid smoke, i.e.0 %, 1 %, 2 %, 3%, 4% and 5 %, and second factor is the pyrolysis temperature of Laban liquid smoke, i.e.350oC, 400oC and 450oC. Every treatment had 5 replications. The toxicity testing had done by in vitro methodusing PDA medium mixed with the liquid smoke.The concentration of 5% is anti-fungal and can beconcidered as inhibitor for Aspergillus nigers hyphal growth to 100%, the result of the researeh showed thatconcentration 5% of laban wood liquid smoke is optimum to inhibit A. niger fungus growth. Key word : Aspergillus niger, liquid smoke, labanwood, antifungal, Pinus merkussi.